Transnational Interaction and Community Engagement: The Role of Indonesian Migrant Workers in The Cross-Border Adoption of Qris on Japan Toward SDGS - Muhammad Reza Rustam; Muhammad Fadli Hanafi; Rudy Yusuf (Riviera Publishing, 2026)
Digital payment systems have transformed transnational financial interactions by reshaping the social and economic dynamics of diaspora communities across borders. This research aimed to describe and analyze several key issues discussed in the results and discussion section: (1) QRIS and the Indonesian economy, (2) QRIS expansion to foreign countries, (3) opportunities for Indonesian migrant workers in Japan, and (4) strategies for optimizing QRIS utilization in Japan. A mixed-methods approach was employed by combining qualitative and quantitative methods. Based on the simulation results and the mapping of opportunities and challenges related to QRIS implementation among Indonesian migrant workers (Pekerja Migran Indonesia/PMI) in Japan, if 35% of PMI conducted 20 transactions per month with an average transaction value of ¥3,500 (±IDR 393,000), the potential foreign exchange generated would reach IDR 46.22 billion annually. This potential would increase to IDR 105.64 billion if QRIS adoption reached 80% of the total PMI population. The estimated value could be even higher if annual Indonesian tourist visits to Japan were also included in the calculation. The expansion of QRIS in Japan could be accelerated through the active role and community engagement of migrant workers as early adopters and financial intermediaries within their social networks in Japan. The findings of this study are expected to contribute to the broader discourse on transnational digital finance and expand research on technology-based financial inclusion within diaspora communities, particularly among Indonesian migrant workers in Japan.